2014
DOI: 10.1016/j.brainres.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Lithium protects against glucocorticoid induced neural progenitor cell apoptosis in the developing cerebellum

Abstract: Respiratory dysfunction is one of the most common causes of death associated with premature birth (Barton et al., 1999). In the United States, 7–10% of pregnant women receive antenatal glucocorticoid (GC) therapy (Matthews et al., 2004), while approximately 19% of very low birth weight infants receive postnatal GC therapy (Jobe, 2009). Clinical research suggests that GC treatment causes permanent neuromotor and cognitive deficits (Yeh et al., 2004) and stunts cerebellar growth (Parikh et al., 2007; Tam et al.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…Brains were harvested and postfixed in 4% PFA for 24 h at 4 °C, embedded in 3% agar, and serially sectioned in the sagittal plane at 75 μm on a vibratome. Every 8th section was immunolabeled for activated caspase 3 (AC3) as previously described [17]. Commitment to cell death occurs prior to cell surface expression of AC3, making AC3 a reliable marker of apoptosis.…”
Section: Methodsmentioning
confidence: 99%
“…Brains were harvested and postfixed in 4% PFA for 24 h at 4 °C, embedded in 3% agar, and serially sectioned in the sagittal plane at 75 μm on a vibratome. Every 8th section was immunolabeled for activated caspase 3 (AC3) as previously described [17]. Commitment to cell death occurs prior to cell surface expression of AC3, making AC3 a reliable marker of apoptosis.…”
Section: Methodsmentioning
confidence: 99%
“…Additional benefits of lithium therapy include neuroprotective [14,15], anti-inflammatory [16] and anti-apoptotic effects [17], which have been exploited to treat central nervous system trauma [18,19] and chronic neurodegenerative diseases, such as Huntington’s disease, amyotrophic lateral sclerosis and Parkinson’s disease [20,21]. In the peripheral nervous system, it has been shown that lithium administration can foster functional recovery and re-myelination after injury [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, brains were immunolabeled for AC3 per laboratory protocol [9, 13]. Briefly, six hours after initial injection, pups were deeply anesthetized and transcardially perfused via the left ventricle with 4% paraformaldehyde in 0.1M Tris buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Semiquantitative analysis of GINA was performed as described previously [8, 9, 13]. Briefly, a rater blind to treatment scored each cerebellum by examining several midsagittal sections per animal and evaluating the amount of AC3 positive NPCs in the EGL based on the following scale:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation